The importance of nursing management in the Intensive Care Unit: Integrative literature review (Research, Society and Development, 2022)
The aim of this study was to identify the scientific evidence available about nursing management in the intensive care unit. It is an integrative literature review, with the scope of verifying national and international publications related to the theme, in order to highlight knowledge in the scientific field. 1,867 scientific articles published in the 5-year period were found in the databases, after application of the selection criteria, only 08 articles that constituted the final sample of the research. The managerial actions of the nurse are fundamental to achieve the quality of the assistance provided, there is a challenge in the nurse's performance when considering the political and organizational aspects involved in the managerial models. It is essential that more studies on the subject are carried out to compose the national and international scientific literature.